Rodzima klasyka filmowa w świadomości zbiorowej polskich widzów. Opinie Polaków o polskich filmach i ich postawy wobec polskiej produkcji filmowej - Giza, Barbara; Wenzel, Michał (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The text discusses the social understanding of the film canon. The analyses is based on the results of the social research “Poles about Polish films. Opinions of Poles on Polish cinema and their attitudes towards Polish film production” conducted in 2019. The research findings show how Polish audiences think about the Polish film canon and how they define it, referring to their own film experiences, attitudes towards Polish productions and to beliefs about the influence of Polish cinema on culture.